2015
DOI: 10.1007/s12282-015-0599-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics of breast cancer and trends in the management of breast cancer patients in Japan: Based on the Breast Cancer Registry of the Japanese Breast Cancer Society between 2004 and 2011

Abstract: Although this study was based on the registry database, several unique clinicopathological characteristics of breast cancer in Japan have been unveiled. Our results suggest that recent trends in the management of breast cancer patients in Japan were strongly followed by clinical evidence that originated from a number of clinical trials worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 18 publications
4
49
1
Order By: Relevance
“…The rate of HER2 positivity of 37% found in microinvasive carcinoma in the present study was higher compared with the rates of earlier reports on invasive breast cancer in Japanese (12%–15%) 22 23. The characteristics found for HER2-positive microinvasive breast cancer can be summarised as follows: (1) high grade; (2) large comedo (>450 µm); (3) high TIL and CD8+ TIL; (4) healing phenomenon and (5) high rate of cluster-like invasion.…”
Section: Discussioncontrasting
confidence: 87%
“…The rate of HER2 positivity of 37% found in microinvasive carcinoma in the present study was higher compared with the rates of earlier reports on invasive breast cancer in Japanese (12%–15%) 22 23. The characteristics found for HER2-positive microinvasive breast cancer can be summarised as follows: (1) high grade; (2) large comedo (>450 µm); (3) high TIL and CD8+ TIL; (4) healing phenomenon and (5) high rate of cluster-like invasion.…”
Section: Discussioncontrasting
confidence: 87%
“…In addition, the JBCS Registry reported that the proportions of ER and PgR positivity were 75.7% and 62.3% among those registered in 2005, respectively 11 . Furthermore, with respect to histological type of breast cancer, the JBCS Registry reported proportions of 82.9%, 8.2% and 8.9% for invasive carcinoma, non-invasive ductal carcinoma and remaining types (including non-invasive lobular carcinoma and special and other types), respectively, among breast cancer patients registered in 2004 20 . Our results were in accordance with the results of this relevant registry.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, studies on breast cancer in Japan between 2004 and 2011 showed that although the annual rates of patients treated with BCS increased until 2006, this increase stopped in 2007 and plateaued at approximately 60% thereafter. The proportion of modified radical mastectomy steadily decreased between 2004 and 2011 while that of simple mastectomy increased during the same period [22]. …”
Section: Discussionmentioning
confidence: 99%